The design, construction, and testing of a radiated emission transcuder as an alternative to an open-area test site in the measurement of electromagnetic interference - Langomez, Rommel I. (Animo Repository, 1999)
This paper presents the design, construction, and testing of an integrated miniature open-area test site (IMOATS) that is sensitive to vertically and horizontally polarized radiation emission emanating from a simulated electromagnetic interference (EMI) source. This transducer serves as an alternative to an open-area test site which is the preferred method in performing radiated emission tests. First, an open-area test site was established according to an ANSI and IEEE standards. Second, a monoconical stand was designed and constructed that is primarily sensitive to vertically polarized radiated emission. Third, the stand was tested for sensitivity to horizontally polarized radiated emissions by using a horizontal dipole.A successful implementation of the results of this study can provide a compact and low-cost alternative to an open-area test site. This enables the Philippine electrical, electronics, and telecommunications industry to begin satisfying the need for low-cost electromagnetic compatibility (EMC) test methods in the global market.